2007
DOI: 10.1007/s11747-007-0057-x
|View full text |Cite
|
Sign up to set email alerts
|

Consumer creations of product meaning in the context of African-style clothing

Abstract: In this article, the author conducts a multisite ethnography to examine how US consumers construct product meanings and assign them to African clothing worn in different consumption settings. Contextual product meanings both emphasize the changing role of the consumption setting and reveal the consumer's use of place. A model emerges from the data to show that consumers establish contextual product meanings through the use of interpretive frameworks, or meaning domains, and that the consumption setting influen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
17
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 52 publications
0
17
0
Order By: Relevance
“…According to social construction theory, however, the value assessment is part of the social reality and becomes more than individual and subjective: value must also be understood as part of a collective and intersubjective context. For example, the understanding of value in fashion is more or less socially constructed (DeBerry-Spence, 2008). Collective social forces often have a dominant role, but individual needs, preferences, habits and values play an important part in both service co-creation and value assessment, both from the customer's and the provider's perspective.…”
Section: Value-in-usementioning
confidence: 99%
“…According to social construction theory, however, the value assessment is part of the social reality and becomes more than individual and subjective: value must also be understood as part of a collective and intersubjective context. For example, the understanding of value in fashion is more or less socially constructed (DeBerry-Spence, 2008). Collective social forces often have a dominant role, but individual needs, preferences, habits and values play an important part in both service co-creation and value assessment, both from the customer's and the provider's perspective.…”
Section: Value-in-usementioning
confidence: 99%
“…Likewise, Colin Campbell has suggested that consumption 'far from exacerbating the 'crisis of identity' is indeed the very activity through which individuals commonly resolve the issue' (Campbell, 2004: 30). 6 Empirical studies confirm the consumers' motivation to create a sense of sequence or narrative self through consumption practices (DeBerry-Spence, 2008;Gould and Lerman, 1998;Murray, 2002). Arnould and Price (2000 ) argue, for instance, that one way personal narratives are created and sustained is through authenticating acts, in which consumption objects and practices are felt as an expression of the 'true self' (see also Belk, 1988).…”
Section: Why?mentioning
confidence: 98%
“…Furthermore, there have been a selected number of studies on youth culture and fashion in Africa (DeBerry-Spence, 2008;Gondola, 1999;Louchran, 2009;Thomas, 2003), however, with little focus on fashion adoption but rather exploring style identities through fashion. As a result, there seems to be a lack of literature on a South African youth culture and factors that influence their decisions to adopt fashion.…”
Section: Introductionmentioning
confidence: 99%